Nurses' experiences of communicating respect to patients: Influences and challenges. (November 2019) - Clucas, Claudine; Chapman, Hazel; Lovell, Andrew
Background: Respectful care is central to ethical codes of practice and optimal patient care, but little is known about the influences on and challenges in communicating respect. Research question: What are the intra- and inter-personal influences on nurses' communication of respect? Research design and participants: Semi-structured interviews with 12 hospital-based UK registered nurses were analysed using interpretative phenomenological analysis to explore their experiences of communicating respect to patients and associated influences. Ethical considerations: The study was approved by the Institutional ethics board and National Health Service Trust. Findings: Three interconnected superordinate themes were identified: 'private self: personal attitudes', 'outward self: showing respect' and 'reputational self: being perceived as respectful'. Respectful communication involved a complex set of influences, including attitudes of respect towards patients, needs and goals, beliefs around the nature of respectful communication, skills and influencing sociocultural factors. A tension between the outward self as intended and perceived presented challenges for nurses' reputational self as respectful, with negative implications for patient care. Discussion: The study offers an in-depth understanding of intra- and inter-personal influences on communicating respect, and sheds light on challenges involved, helping provide practical insights to support respectful care. Conclusion: Findings stress the need for improved conceptualisations of respect in healthcare settings to formally recognise the complex attitudinal and socially constructed nature of respect and for appropriate professional training to improve its communication.